Work culture in CTRM Aero Composites: individualism vs collectivism / Aimie Asfarinna Azman - Azman, Aimie Asfarinna (Faculty of Business and Management, 2011)
This study is a research on the work culture practiced by employees at Composite Technology Research Malaysia Aero Composites (CTRM AC) located at Batu Berendam, Melaka whereby the researcher was in internship in the organization for five months to complete the study in Bachelor of Business Administration (Hons) International Business. This study will focus on the individualism and collectivism dimension with four main objectives. First is to determine whether employees at CTRM AC can do their job on their own. Second is to identify whether employees at CTRM AC can work with minimum supervision from their superior or top management. Third objective is identify whether the employees at CTRM AC is multitasking or not and last but not least to identify other factors that can enhance their job satisfaction performance.